Kazakh journalism education in the context of modern realities (Herald of Journalism, 2025)
The purpose of this study is to explore the current thoughts of academics and media industry professionals about journalism education, which is considered to be the most important in training professionals. A mixed method was used, which included phenomenology and descriptive research, and quantitative data were collected from both groups. The study found that both groups, academic and professional, agreed that students need both education and experience. Students, in addition to the ability to use digital technologies, should also be able to write creatively that engages and engage their audiences in all media. The most relevant skills were the ability to recognize errors, false arguments, manipulation, separate facts from opinions, analyze concepts, ask the right questions, approach content critically, and read widely. As a result, one of the recommendations was that journalism education programs should be equipped with practical skills such as video reporting, editing, writing, and social media trends.According to the Unified Higher Education Platform, there are 43 bachelor's degree programs in journalism, which vary greatly. Some emphasize more logical approaches, others emphasize the theoretical approach, emphasize history, ethics, laws, rights of journalists, and others are completely inclined to teach skills or a practical approach. But among the many opinions voiced, it is worth noting that the training of students should not emphasize a career in news services, since journalism is too important a profession to delegate it exclusively to one media outlet.
Keywords: journalism education, journalist profession, educational programs.